Identifikasi Jenis Tumbuhan Paku (Pteridophyta) di Jalur Pendakian Gunung Nokilalaki Desa Tongoa Kecamatan Palolo Kabupaten Sigi - Asmara, Dudun Candra; Jamhari, Mohammad; Febriawan, Aan; Trianto, Manap; Astija, Astija; Nurdin, Musdalifah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The purpose of this study was to identify the types of ferns (Pteriodophyta) found on the Nokilalaki Mountain Climbing Trail, Tongoa Village, Palolo District, Sigi Regency. This type of research is a qualitative descriptive research using the exploration method and free collection sampling techniques. This study aims to describe existing phenomena. In it there are efforts to describe, record, and analyze the conditions that are happening factually. The results of the study conducted on the Mount Nokilalaki Climbing Trail, Tongoa Village, Palolo District, Sigi Regency obtained 26 types of ferns consisting of 4 classes, 6 orders, 14 families. Of the 26 types of ferns (Pteridophyta) found, namely Dryopteris filix-mas, Dryopteris marginalis, Rumohra adiantiformis, Neprolepis cordifolia, Athyrium macrocarpum, Asplenium nidus, Asplenium polyodon, Davallia trichomanoides, Microsorum fortune, Pteris biaurita, Nephrolepis biserrata, Nephrolepis sp, Microlepia speluncea, Microsorum pustulatum, Pyrrosia lanceolata, Pyrrosia philoselloides, Microsorum punctatum, Vittaria elongate, Angiopteris evecta, Cristella dentate, Selaginela wildewoii, Selaginela involvens, Selaginela sp, Selaginella apoda, Huperzia lucidula. Hymenophyllum sp.